EVALUATING DEGREE OF ACTIVE POWER LOSSES REDUCTION IN THE ELECTRIC POWER LINES WITH REACTIVE POWER COMPENSATION - V. N. Radkevich; M. N. Tarasova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers evaluation procedure for the degree of active power losses reduction in the power transmission lines under 1 kV and 6–10 kV of the systems of electric power supply of industrial enterprises with compensating installations mounted at the side of the customer. The capacitor installations conform to the applied voltage level and factor in dielectric losses in the capacitors. The voltage at the compensating device terminal changes from 0.95 to 1.05 of the capacitors nominal voltage. The study did not account for reactive power losses in the line, nor did it for its charge capacity, conditioned by relative shortness of the cable lines generally operating in the mains of industrial enterprises. For this reason, the quantities of reactive power being consumed and generated by the transmission line are negligible and do not significantly affect the reactive power flux. The researchers obtain functional relations that allow estimating the degree of power loss reduction in the transmission line factoring in its explicit initial data. They perform mathematical analysis of the obtained functional relations and study the function by means of derivatives. The function extremum points are found as well as the intervals of its increment and decrement. A graphical research of the obtained functional relation is performed. It is ascertained that reduction of the active power losses is contingent on the line and the capacitor-installation engineering factors, the electrical energy consumer reactive load value as well as the voltage applied to the capacitor installation. The functional relations presented in the article can be employed in scoping calculation necessary for decision making on the reactive power compensation in systems of the industrial facilities electric power supply. Their account will allow a more accurate estimate of technical and economic effect of the capacitor bank installation in the electrical mains under 1 kV and 6–10 kV.